Reconstruction Options Following Wide Excision of Basal Cell Carcinoma of the Face - Khoo, Hau Chun; Kelly, Enda Gerard; Mohd Ali Mat Zain,; Farrah-Hani Imran, (Faculty of Medicine, UKM Medical Centre, 2015)
Basal cell carcinoma is the commonest skin malignancy diagnosed in Malaysia. Surgery is the recommended treatment of choice with the lowest failure rate provided a clear margin is obtained. However, the defect may be too large to be repaired primarily. Formal reconstruction using grafts and flaps should be done to achieve the optimal aim of maintaining the integrity, function and cosmetic patient outcome. Three reconstructive methods are described in this series to restore the facial defect following the wide local excision. The procedures described were peri-alar crescentic advancement flap, nasolabial rotational flap and full thickness skin graft using supraclavicular skin. This series highlights the usage of the procedures based on solid foundation and principles, without compromising the desired outcomes for the patient.